Determination of Optimal Sand Material selection for Sand moulding using DMAIC Method: Indonesia - Aliamran, Suryadi; Karnadi (JURNAL TEKNIK DAN SISTEM INDUSTRI, 2023)
Companies must be able to adapt to internal and external challenges both in terms of business and non-business, as in the current situation there is a Covid-19 pandemic effect. The state of the company is in the state of Covid-19 pandemic, i.e. the company must save on existing processes and materials. One of the materials used in the casting process is RCS (Resin Coated Sand) which is used as a sand mould. In this study, the study of casting companies using RCS materials was taken with the aim of finding the optimal solution in material costs and defects that occur in the motorcycle casting process. By using the direct field observation brainstorming method with the DMAIC method approach it is hoped to identify problems and find optimal solutions for the purpose or target of the company. analysis that the search for alternative materials that can reduce the process defect ratio and correlate with RCS recycling process so that although alternative material prices are more expensive than initial production materials, reduced defect ratios and overall material costs can be considered, there are benefits so that alternative material options can be selected. From the testing of the material, it is found that the defect of the casting product is reduced from the previous condition, i.e. for the defect on average around 1% to 0% and the overall price of the material is the same